The Application of End User Computing Satisfaction (EUCS) to Analyze the Satisfaction of MyPertamina User - Arief Budi Pratomo; Muhammad Ade Kurnia Harahap; Teddy Oswari; Pas Mahyu Akhirianto; Agung Widarman (Jurnal Sistim Informasi dan Teknologi, 2023)
This study measures how satisfied users are with the application system in order to ascertain both the degree of users' satisfaction and the variables affecting users' contentment. Content, accuracy, format, usability, and timeliness are the five characteristics that make up the End User Computing Satisfaction (EUCS) research model, which is used in this study's quantitative methodology. A purposive selection method was employed to choose the sample for this study, which included 200 respondents. SmartPLS 3.0 software is utilized for the data analysis procedure. One of the five investigated hypotheses was ruled out. Thus, content, correctness, usability, and timeliness are the aspects that can influence application user satisfaction. While the format variable has no impact on program user pleasure. So that the findings of this study can be recommended to companies as authorities to pay more attention to the aspects that affect application user happiness as described.